The Invisible Economy: Personal Data as a New Commodity in the Digital Economy - Oli Gretia Nitsae (PT. Anagata Sembagi Education, 2026)
The digital economy has quietly transformed personal information into one of its most valuable, yet least visible, commodities. This article examines how personal data is extracted, valued, and exchanged within contemporary digital markets, framing this phenomenon as an